The role of English language teachers in providing students with self-learning skills from school principals Perspective in Ajloun Governorate - Bashayreh, Mufeedeh Khader Ibrahim (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the role of English language teachers in providing students with self-learning skills from school principals perspective in Ajloun Governorate, the researcher used the descriptive approach, and the study Sample consisted from (85) Female and male of school principals, chosen randomly, to collect data Questioner used, which consisted (20) paragraph. The result of SPSS analysis shown that the degree of the role of English language teachers in providing students with self-learning skills from school principals perspective in Ajloun Governorate was moderated with average (3.48 out of 5) , The finding also showed there is no statistically significant differences at (α≤0.05) refers to principals sex (male and female). In addition, there were statistically significant differences refers to principal’s years of experience in favor of (10 years and more). The study recommended activating self-education in schools in Ajloun Governorate, especially in English language lessons, and providing tools, requirements and programs for the application of self-education.